Numerical investigation of wind influences on photovoltaic arrays mounted on roof. Issue 1 (1st January 2019) - Li, Jiayang; Tong, Lewei; Wu, Jianming; Pan, Yeming
Abstract : The wind-induced response of photovoltaic (PV) panel installed on building roof is influenced by the turbulence induced by the pattern of both panels and roofs. Different roof types cause different flow patterns around PV panels, thus change the flow mechanism exerted on PV panels. In this study, the effects of roof types, heights and the PV array layouts on the net wind loads of the PV panel is investigated. The software Fluent is adopted and the three-dimensional Reynolds-averaged Navier–Stokes (RANS) method is used for numerical analysis. The rationality and accuracy of the numerical results obtained from the current study are verified through comparison with the results of wind tunnel experiments. The maximum wind uplift on the PV panels increases with the panel tilt angle for two types of roofs, but decreases with the increase of the PV array edge setback. Moreover, the maximum wind uplift also increases with the roof clearance within a certain range. Both the row spacing of PV array and the building height have a great effect on the maximum aerodynamic uplift for gable roofs, whereas both of them have slight influence for flat roofs.